Penyelesaian Terhadap Wanprestasi Pengguna Aplikasi Go-Jek Berupa Pembatalan Orderan Sepihak Terhadap Pengemudi (Driver) Go-Food Di Wilayah Kota Payakumbuh - Harahap, Ikhyar Rizki; Syuryani, Syuryani; Rusli, Benni (Wajah Hukum, 2023)
Gojek Indonesia is a technology company, not a transportation company that provides transportation services. The service features available on the go-jek application are go-food, which is a delivery service provided by go-jek companies to buy and deliver food orders to their users. The large number of consumers who use this application always cancel orders unilaterally which results in default in an agreement. This study discusses the settlement of defaults on the use of the gojek application in the form of unilateral cancellation of orders for gofood drivers in the Payakumbuh City area. This research raises two problems, namely What is the process for the birth of an agreement between gojek drivers and go-jek application users in food ordering activities, What is the settlement of compensation for defaults on gojek application users in the form of unilateral cancellation of orders against go-jek drivers? Food. This study uses the Juridical Empirical method. The data sources used are Primary Data through interview studies and document studies and Secondary Data through primary legal materials, secondary legal materials and tertiary legal materials. The results of the study show how the process of the birth of an agreement between go-jek drivers and go-jek application users in food ordering activities and settlement of compensation for defaults on go-jek application users in the form of unilateral cancellation of orders against go-food drivers. The implementation that occurs for consumers purchasing food and drinks through the online ordering application, as mentioned, does not always go well. There are also actions that can harm other parties in their implementation, especially when ordering food and drinks using an online application, in other words, consumers do not come directly to the places where the food and beverage sellers are concerned. Default means negligence, negligence, default, not fulfilling its obligations in the agreement. Based on the Consumer Protection Act, there are rights and obligations held by business actors.